INOCULAÇÕES COM BACTÉRIAS PROMOTORAS DE CRESCIMENTO EM MILHO PODE REDUZIR ADUBAÇÃO NITROGENADA DE COBERTURA - Thais Almeida Silva, Pérlla; Ferreira Vetruve, Italo; Leonel Alves , Melissa; Pisa Andrade, Beatriz; Carvalho Minhoto Teixeira Filho , Marcelo; Eduardo da Silva Oliveira , Carlos (ANAIS DO ENIC, 2026)
-